An Algerian endemic species in danger to disappear due to pandemic, Origanum vulgare subsp. glandulosum (Desf.) Letsw (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Adouani I, Boulaacheb N. 2022. An Algerian endemic species in danger to disappear due to pandemic, Origanum vulgare subsp. glandulosum (Desf.) Letsw. Biodiversitas 23: 3147-3155. Algeria is known for its rich flora, and the traditional use of medicinal plants is very ancient. The use of medicinal plants is extremely intensified during the COVID-19 pandemic. To enumerate the most used species by the Algerian population, two ethnobotanical surveys have been conducted from October to December 2021. Thirty herbalists were interviewed, and 165 respondents participated in an online survey. The results showed that a total of 25 species belonging to 16 botanical families had been reported to be used in different modes of preparation to prevent or treat the infection. One of the locally used species is Origanum vulgare subsp. glandulosum (Desf.) letsw. Generally, Algerians internally use this species as a tea or as a powder preparation with honey or only the powder with water to treat many health problems such as diarrhea, colds, coughs, respiratory infections, rheumatism, and menstrual symptoms. Otherwise, the powder of the plant is externally used alone or with olive oil to cure several illnesses such as rheumatism, and skin irritations. Due to the extensive use of this species during the pandemic, the demand in the market has increased, as also the price. Herbalists reported that they have received between 30-300 people affected or not by COVID-19 per day. The price went from 1500-5000 DA per kg (10.33-34.42 USD). Therefore, the increase rate is expected to be 50-80% for the demand, and 50-90% for the price. This increase in demand during COVID-19 has led to an exaggerated and random collection of species at different stages of the development of the plant. Although O. vulgare subsp. glandulosum is a common species, but it can be rare or even disappear due to the extensive collection without protective measures due to COVID-19. Therefore, it is important to engage policies for the conservation and cultivation of O. vulgare subsp. glandulosum.